2018
DOI: 10.1177/1082013218769168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maltodextrin reduction and native agave fructans addition on the physicochemical properties of spray-dried mango and pineapple juices

Abstract: The effects of the partial replacement of maltodextrin by native agave fructans on the characteristics of spray-dried pineapple and mango powder were evaluated in this study. An experimental 3 design, three concentrations of maltodextrin (5, 7, and 10%), three concentrations of native agave fructans (0, 2, and 4%), and three feed temperatures (110, 115, and 120  ℃) were used. The results using the treatment in which only maltodextrin was used as a reference indicated that an increment in the inlet temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The particles produced with the optimized parameters showed smooth surfaces with few cavities and dents (Figure ). This morphology may be attributed to the mechanical atomization, airdrop interaction and capsule cooling, as supported by Jimenez‐Sánchez et al (). The average particle size D 43 was 9.2 ± 0.3 μm, which it is higher in comparison with 3–5 μm for spray‐dried guava juice (Osorio et al, ), but lower than 10,97–14,48 μm for spray‐dried guava pulp (Shishir et al, ).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The particles produced with the optimized parameters showed smooth surfaces with few cavities and dents (Figure ). This morphology may be attributed to the mechanical atomization, airdrop interaction and capsule cooling, as supported by Jimenez‐Sánchez et al (). The average particle size D 43 was 9.2 ± 0.3 μm, which it is higher in comparison with 3–5 μm for spray‐dried guava juice (Osorio et al, ), but lower than 10,97–14,48 μm for spray‐dried guava pulp (Shishir et al, ).…”
Section: Resultsmentioning
confidence: 60%
“…The values for hygroscopicity of guava powder ranged between 21.9 and 27.8 g of water/100 g of dry matter, like 20.39-34.04 g of water/100 g of dry matter reported for the spray-dried tamarind pulp (Muzaffar & Kumar, 2015), but slightly higher than 14.46 and 20.68 g of water/100 g of dry matter in spray-dried beetroot juice (Bazaria & Kumar, 2016), 14.3-19.5 g of water/100 g of dry matter in spraydried orange juice (Islam et al, 2016), as well as 16.6-18.2 g of water/100 g of dry matter in spray-dried mango juice and 16.3-17.4 g of water/100 g of dry matter in spray-dried pineapple juice (Jimenez-Sánchez, Calderon-Santoyo, Ortiz-Basurto, Bautista-Rosales, & Ragazzo-Sánchez, 2018).…”
Section: Hygroscopicitymentioning
confidence: 99%
“…Cellulose nanofibrils offer structural and mechanical properties and act as a thickener and a physical barrier allowing stabilization of the interface oil/water, what contributes to the improvement of the properties of the essential oil microparticles. Ragazzo-Sánchez, 2018;Rocha, Trindade, Netto, & Favaro-Trindade, 2009). Polymers of carbohydrates, highlighting gum Arabic (GA) and maltodextrin (MD), have been widely used as encapsulating agents; however, the difficulty of finding a material that provides all the requirements to act as a suitable encapsulant, makes it necessary to use them in combination.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Spray‐drying efficiency, emulsion properties, and microcapsules stability depend, among other factors, on the wall material (García‐Lucas et al, ; Medina‐Torres et al, ), therefore being considered an important factor in the quality of dried product. For the selection of suitable encapsulating material should be considered its nonreactivity with the core material, the process used to form the microparticles, and the release mechanism (Jimenez‐Sánchez, Calderón‐Santoyo, Ortiz‐Basurto, Bautista‐Rosales, & Ragazzo‐Sánchez, ; Rocha, Trindade, Netto, & Favaro‐Trindade, ).…”
Section: Introductionmentioning
confidence: 99%
“…Native agave fructans are a heterogeneous mixture of branched fructose polymers, linked by glycosidic linkages of fructose–fructose β (2−1) and β (2−6), with intermediate or terminal glucose units with degrees of polymerization (DP) between three and 29 [ 1 ]. These fructans have potential applications due to their proven beneficial effects on human health, such as the prebiotic effect, as well as decreasing the body mass index, total body fat and triglyceride levels [ 2 , 3 , 4 , 5 ] and their technological applications as encapsulating agents and as substitutes for fat in food [ 6 , 7 , 8 , 9 , 10 ]. However, it has been reported that fructans with different DP differ in their prebiotic effectiveness and techno-functional properties, as well as in the removal of low-molecular weight sugars such as glucose, fructose and sucrose, increasing the purity and functionality of fructans.…”
Section: Introductionmentioning
confidence: 99%